Perencanaan Arsitektur Data dan Aplikasi pada Divisi Marketing Perusahaan Ekspedisi dan Distribusi X - Karjadi, Felicia Novita; Dewi, Lily Puspa; Yulia, Yulia (Jurnal Infra, 2015)
PT. X is a company which engaged in distribution and sea lane expedition since 2005. The products that distributed by PT. X are cement and fertilizer subvention. In support of the business process, marketing department of PT. X doesnât have yet any information system, so that marketing department is using outsource service to support its business process.Marketing department of PT. X needs analysis and design of enterprise architecture information system. Enterprise Architecture Planning is used for the framework. First step of analysis and design of enterprise architecture is analysis of business model and company business strategic. The next step is analysis of recent information technology, understanding the IT problems, and the needs of new IT for the future. After that creating data architecture design and application architecture design based from data and information which obtained from the company.Â The results of analysis and design of enterprise architecture information system is data architecture report and application portfolio which useful to support business process and information technology improvement for marketing department for PT. X.